Advancements in bifunctional catalysts for unitized regenerative fuel cells: exploring polaronic conduction and heterostructure designs - Sharma U.; Jha P.K.; Jha P.A.; Singh P. (My University, 2025)
This study investigates the development and performance evaluation of a bifunctional catalyst tailored for unitized regenerative fuel cells (URFCs), capable of facilitating both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in fuel cell and electrolyzer modes. The primary challenge addressed is the creation of electrocatalysts exhibiting high activity and corrosion resistance for oxygen reduction and water oxidation at the oxygen electrode. A novel catalyst structure based on La0.5Sr0.5Fe0.5Ti0.5O3(LSFT), i.e. LSFT/ZnO/LSFT with a thickness of ∼ 2 μ m, is explored within an environmentally friendly medium. This catalyst demonstrates superior performance characteristics, including reduced overpotential in HER and enhanced stability during oxygen/hydrogen evolution processes in neutral medium. This study identifies the formation of interfacial polarons and polaronic charge modulation resulting from the incorporation of ZnO in LSFT, leading to multifunctional OER/HER behavior. Notably, the proposed interfacial small polaron mechanism offers valuable insights into complex interfacial phenomena and holds promise for applications in diverse heterostructures involving layered 2D materials and transition metal oxides. Moreover, the robust LSFT/ZnO/LSFT catalyst exhibits exceptional stability, maintaining for 168 h of oxygen evolution at a constant potential of approximately 1.66 V for a current density of 1 A cm−2 in a neutral medium. These findings mark a significant advancement in URFC technology and present promising avenues for clean energy storage solutions. © 2024 IOP Publishing Ltd.